Structural, magnetic and dielectric properties of FeշO3-TeOշ glass with starting materials of different particle size - Nadakkavil Alassan, Zarifah (2012)
Tellurite based glasses have physical properties that are important for both fundamental and practical applications which are low melting temperature, high dielectric constant,high refractive index, good infrared transmittance and high chemical durability while oxide glass with iron oxide are important due to their magnetic, optical and electrical properties. Hence we proposed to study the structural, magnetic and dielectric properties of Fe2O3-TeO2 glass with different particle size of the starting materials. Glasses in a wide range of composition in the binary system (Fe2O3)x-(TeO2)1-x where x ranges from 0.10 to 0.30 in the interval of 0.05 have been prepared using different sizes of the starting materials by conventional melt quenching technique with Fe2O3 and TeO2 as the starting raw materials. All the glasses in the present work have been confirmed to be amorphous by X-Ray diffraction (XRD) analysis. The short range structures of those binary glasses were examined by Fourier-transform infrared (FTIR) spectroscopy. The density of the glasses was determined by Archimedes Principle. From the empirical data, molar volumes have been computed. Glass stability and glass forming ability was determined using Differential Thermal Analysis (DTA) curve. Magnetic measurement has been performed at room temperature using vibrating sample magnetometer (VSM). The dielectric properties of the samples were also measured using Novocontrol Novotherm High Dielectric Resolution Analyser. The density of the FT series decreases from 5.26 gcm-3 to 5.09 gcm-3 while FTN series decrease from 5.37 gcm-3 to 5.06 gcm-3 with the addition of Fe2O3 due to the replacement of high density TeO2 with Fe2O3. The molar volume of the glass samples shows a reverse trend compared to the density which increases with increasing Fe2O3 where FT series increase from 30.28 cm3 mol-1 to 31.18 cm3 mol-1 and FTN series increase from 29.71 cm3 mol-1 to 31.35 cm3 mol-1. The magnetization analysis shows that all samples have soft magnetic properties. FT glass series were found to exhibit paramagnetic behavior. Binary samples using nano material with x=0.30 has paramagnetic behavior with contribution of superparamagnetic behaviour. The results show that the dielectric permittivity and dielectric loss decrease with frequency and increase with temperature. The behavior of dielectric curves was modeled using equivalent RC circuit consisting combinations of dispersion barrier C*A, quasi – dc, C*B, resistance R, and non dispersive capacitance C∞. The conductivity plot shows two regions, dispersive and flat. This is due to the DC conduction and hopping mechanism. The hopping will take place between the Fe2+ and Fe3+ ions (Fe2+ → Fe3+ + e−) among the different factors, which influence the conductivity.